Trend and Determinants of Mortality Among Women of Reproductive Age: A Twelve-Year Open Cohort Study in Eastern Ethiopia - Dheresa, Merga; Tura, Abera Kenay; Daraje, Gamachis; Abebe, Mesfin; Dingeta, Tariku; Shore, Hirbo; Dessie, Yadeta; Yadeta, Tesfaye Assebe (Frontiers in Global Women's Health, 2021)
Abstract Background: With only less than a decade left to 2030 sustainable development goal (SDG) understanding the burden and trends of women's reproductive age (WRA) mortality is essential for designing appropriate interventions. For several low-income countries, such data are often lacking or sometimes extrapolated from non-representative facility-based studies. In this paper, we presented trends, causes, and determinants of mortality among reproductive-age women under follow-up for 12 years through the Health and Demographic Surveillance System (HDSS) is located in eastern Ethiopia. Methods: We used 12 years (2008 to 2019) open cohort data of women aged 15-49 years living in Kersa HDSS in Eastern Ethiopia. In the HDSS, data on socio-demographic and basic household conditions are recorded for every household member at enrollment, and data on vital events births, deaths, and migration were collected and updated biannually as the event happened. Mortality was determined by automated verbal autopsy (InterVA). We assessed women's reproductive age mortality trends and the associated determinants using crude and adjusted Cox regression models. Results: In the twelve years cohort, we followed 74,790 women of reproductive age for 339,909.26 person-years-at-risk of observation (PYO) of whom 919 deaths happened. Overall, the standardized mortality rate was 270 per 100,000 PYO. There was a notable increase in mortality in the first three years (2009 to 2011) and then after declined significantly (p-=0.0001) until 2019. Most of the dead were happened by HIV/AIDS (27.88%) and pulmonary tuberculosis (10.62%). In the adjusted Cox regression analysis, the hazard of death was higher among rural residents (AHR, 2.03: 95% CI: 1.60-2.58), unemployed women (AHR, 1.50: 95% CI: 1.19-1.89), and women with no formal education (AHR, 1.24: 95% CI: 1.01-1.52). Conclusion: The study showed that many women of reproductive age are still dying mainly due to causes for which preventable strategies are known and have been successfully implemented. The identified main causes of death and a higher mortality hazard among rural residents, unemployed women, and those with no formal education need attention and effective implementation in achieving the Sustainable Development Goal targets and beyond.